A Mean Value Formula for Elliptic Curves. (25th August 2014) - Feng, Rongquan; Wu, Hongfeng
Abstract : It is proved in this paper that, for any point on an elliptic curve, the mean value ofx -coordinates of itsn -division points is the same as itsx -coordinate and that ofy -coordinates of itsn -division points isn times that of itsy -coordinate.